STRATEGI PERUSAHAAN DAN KINERJA PERUSAHAAN: PERAN MODERASI TATA KELOLA PERUSAHAAN PADA INDUSTRI ENERGI INDONESIA - Holanda, Alya Dinarty; Sari, Alfiana; Marza, Qayla Aisyah; Putri , Faradillah Anisa; Alyana, Dina (Management Insight: Jurnal Ilmiah Manajemen, 2026)
This study aims to analyze the effect of Corporate Strategy on Firm Performance and to examine the moderating role of Corporate Governance in that relationship among energy sector companies listed on the Indonesia Stock Exchange. This study employs a quantitative approach using a panel data design for the period 2022–2024, with 243 observations. Corporate Strategy is measured using eight content analysis-based indicators, while Corporate Governance is measured through three supervisory mechanism indicators. The analysis method used is Moderated Regression Analysis (MRA). The results indicate that Corporate Strategy has no significant effect on Firm Performance (sig. 0.113), Corporate Governance has no significant effect on Firm Performance (sig. 0.341), and Corporate Governance does not significantly moderate the relationship between Corporate Strategy and Firm Performance (sig. 0.288). These findings suggest that the performance of energy companies in Indonesia is more influenced by external factors such as commodity price fluctuations and regulatory policies than by internal strategy and governance mechanisms. Keyword: Corporate Strategy; Corporate Governance; Firm Performance; Energy Industrial; Moderation